High intra-tumoral and serum matrix metalloproteinase 9 levels are associated with reduced survival of patients with glioblastoma and brain metastases - Kaisman-Elbaz, Tehila; Haddad-Shlaifshtein, Snir; Eskira, Yael; Merkin, Vladimir; Dumanis, Guy; Turiel, Sivan; Atar-Vardi, Maya; Bari, Romi; Alt, Adi; Zamed, Tali; Rotem-Dai, Noa; Lavrenkov, Konstantin; et al. (Frontiers in Oncology, 2026)
PurposeMatrix metalloproteinase 9 (MMP-9) has been shown to promote glioblastoma invasion and the spread of brain metastases (BM). However, the current literature on its link to patient survival is inconsistent. This study examines intra-tumoral and sera MMP-9 levels and their correlation with overall survival (OS) in patients with glioblastoma and BM.MethodsA total of 69 tumor and pre-operative serum samples were collected from the brain tumor bank at the neurosurgery department of Soroka University Medical Center. These samples were obtained from patients who underwent tumor resection between 2015 and 2021. Clinical and imaging data from 27 glioblastoma patients and 30 individuals with brain metastases were analyzed, measuring and comparing their intra-tumoral and sera MMP-9 levels and activity against those of 12 meningioma patients and 23 healthy controls. Survival analyses were performed to examine the relationship between MMP-9 levels, activity, and clinical parameters.ResultsPatients with glioblastoma and BM showed higher median intra-tumoral MMP-9 levels (8 ng/ml and 4 ng/ml, respectively, p<0.001), increased intra-tumoral MMP-9 activity, and pre-operative serum MMP-9 levels (2.8-fold and 1.8-fold higher than controls, respectively, p<0.001). MMP-9 was found within and between glioblastoma cells. Elevated intra-tumoral and serum MMP-9 levels, but not its activity, were associated with reduced overall survival in glioblastoma and BM patients (15.8 versus 8.4 months, p=0.022). Notably, MMP-9 was easily detectable in the patients’ sera.ConclusionsThis study shows that high intra-tumoral and/or sera MMP-9 levels at diagnosis are linked to significantly worse patient OS. Additionally, intra-tumoral and sera MMP-9 may help identify glioblastoma and BM recurrence or progression. Importantly, sera MMP-9 levels can be monitored over time non-invasively, and an increase might indicate tumor progression.